Supervisi Akademik Kepala Sekolah dalam Meningkatkan Kompetensi Pedagogik pada Kurikulum Merdeka SD Krista Citra Kabupaten Temanggung - Ernawati, Evi; Kusumaningsih, Widya; Ginting, Rosalina BR. (PGRI Kota Semarang, 2024)
SD Krista Citra Temanggung carries out academic supervision in the independent curriculum to improve teacher pedagogical competence. The aim of this research is to describe and analyze the planning, implementation, evaluation and follow-up of the principal's academic supervision in improving pedagogical competence in the independent curriculum at SD Krista Citra Temanggung. The research method is qualitative. Data collection techniques are interviews, observation and document study. Data analysis includes data collection, data reduction, data display, conclusion drawing/verification. Validity test uses triangulation techniques. The research results show that academic supervision planning is carried out cooperatively, creatively, comprehensively, flexibly and continuously. 2) implementation of academic supervision through a coaching paradigm. 3) evaluation of academic supervision is delivered in general and in accordance with supervision principles. 4) follow-up to academic supervision in the form of providing motivation, coaching and solutions. The conclusion of the research is that the principal's academic supervision including planning, implementation, evaluation and follow-up can improve pedagogical competence in the independent curriculum at SD Krista Citra Temanggung.